Eco-Friendly Procedure for Rendering the Antibacterial and Antioxidant of Cotton Fabrics via Phyto-Synthesized AgNPs With Malva sylvestris (MS) Natural Colorant - Sadeghi-Kiakhani, Mousa; Tehrani-Bagha, Ali Reza; Miri, Fateme Sadat; Hashemi, Elaheh; Safi, Mahdi (Frontiers in Bioengineering and Biotechnology, 2022)
There is a growing interest for producing multifunctional cellulose fabrics using green and sustainable technology. In this study, we explored an eco-friendly procedure for dyeing cotton fabrics with Malva sylvestris (MS) as a natural colorant and rendering antibacterial cotton fabric by the silver nanoparticles. MS colorants were extracted from dried petals in water using the ultrasound technique, cotton fabrics were dyed with the extracted MS colorant at 100 °C for 90 min. The colorimetric data and colorfastness properties were investigated in the absence and presence of tannic acid (TA) as a bio-mordant. Results indicated that MS dye had a high potential for reducing the silver nitrate, so that the silver particle size distribution on cotton fabric was obtained 50-80 nm, and TA had a positive effect on the MS extract and reduced Ag on the cotton. Furthermore, the reduction of bacterial growth of the dyed cotton considerably (up to 99%) improved by AgNPs. The colorfastness of the dyed samples with MS colorant against to wash and light was moderate and they were enhanced to good - very good by mordanting.